2023
DOI: 10.3390/v15061225
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Frequency of Detection of Common Respiratory Pathogens in Nasal Secretions and Environment of Healthy Sport Horses Attending a Multi-Week Show Event during the Summer Months

Nicola Pusterla,
Madalyn Kalscheur,
Duncan Peters
et al.

Abstract: Little information is presently available regarding the frequency of the silent shedders of respiratory viruses in healthy sport horses and their impact on environmental contamination. Therefore, the aim of this study was to investigate the detection frequency of selected respiratory pathogens in nasal secretions and environmental stall samples of sport horses attending a multi-week equestrian event during the summer months. Six out of fifteen tents were randomly selected for the study with approximately 20 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In contrast, EHV-1, EHV-4, EIV, ERBV, and S. equi are often associated with clinical disease and are, therefore, considered true respiratory pathogens. Previous studies have shown that true respiratory pathogens can be detected in nasal secretions and/or the environment of silent shedders without signs of clinical disease [ 3 , 4 , 5 , 6 , 7 , 8 , 10 ]. The detection frequency of these latter pathogens in the current study was only 2.22%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, EHV-1, EHV-4, EIV, ERBV, and S. equi are often associated with clinical disease and are, therefore, considered true respiratory pathogens. Previous studies have shown that true respiratory pathogens can be detected in nasal secretions and/or the environment of silent shedders without signs of clinical disease [ 3 , 4 , 5 , 6 , 7 , 8 , 10 ]. The detection frequency of these latter pathogens in the current study was only 2.22%.…”
Section: Discussionmentioning
confidence: 99%
“…The detection frequency of these latter pathogens in the current study was only 2.22%. The authors have shown in previous work that respiratory pathogens can be sporadically detected from the stalls of high-risk horses during non-outbreak situations [ 8 , 10 ]. It is the clustering of stalls (i.e., group of adjacent stalls) testing positive for a specific contagious respiratory pathogen that indicates the silent spread and potential for a disease outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations